Low-carbon urban development hot topics and frontier evolution: a bibliometric study from a global perspective - Cai, Rongjiang; Wang, Xi; Cheng Vong, Chon; Zhao, Shufang; Zhang, Tao (Frontiers in Built Environment, 2024)
The escalating challenges of global climate change have made the development of low-carbon cities—urban areas committed to reducing carbon emissions through sustainable energy use, enhanced building efficiency, and low-carbon transport solutions—a critical area of study. However, there remains a significant gap in the systematic review of the thematic evolution and emerging frontiers within this field. This study addresses this gap by analyzing data from the Web of Science database, initially retrieving 1,743 articles and review articles. Following the PRISMA systematic review guidelines, we refined this selection to 1,648 high-quality publications. Using tools such as CiteSpace and VOSviewer, we conducted an in-depth analysis to identify core authors, prolific countries/regions, leading institutions, and key journals. Our thematic analysis revealed three evolutionary stages in the research on international low-carbon city development. Additionally, we identified seven predominant topics in recent studies: land use, carbon emissions, ecological environment quality, ecosystem services, human health, energy consumption, and economic costs. These findings contribute to a clearer and more comprehensive framework for the development of low-carbon cities, serving as a valuable reference for scholars and practitioners involved in both theoretical and practical aspects of this field.